The Complexity of Comparative Judgments in Assessing Argumentative Writing: An Eye Tracking Study - Gijsen, Marijn; van Daal, Tine; Lesterhuis, Marije; Gijbels, David; De Maeyer, Sven (Frontiers in Education, 2021)
Comparative judgment (CJ) has been recently introduced in the educational field as a means of assessing competences. In this judgement process, assessors are presented with two pieces of student work and are asked to choose which one is better in relation to the competencies being assessed. However, since student work is heterogeneous and highly information loaded, it raises the question as to whether this type of assessment is too complex for assessors to use. Previous research on the topic has operationalized experienced complexity by employing self-report measures, which have been criticized for common problems associated with their use. In our study, we used eye tracking to study 23 high school teachers when they made 10 comparative judgments, and their pupil diameter was used as an indicator of the experienced complexity. This study builds on previous research that integrated Campbell’s theory on task complexity (1988) into CJ. Based on this framework, three hypotheses regarding the role of decision accuracy were formulated and empirically tested. Hypothesis one assumes that the distance between two pieces of student work on the rank-order (rank-order distance) is negatively related to experienced complexity, irrespective of decision accuracy. Hypothesis two assumes that decision accuracy moderates the relationship between rank-order distance and experienced complexity. Hypothesis three builds on hypothesis two by adding a negative relationship between experience and experienced complexity. In all three hypotheses, the average experienced complexity is assumed to vary between assessors, as is the strength of the expected relationships. An information-theoretic approach was used to test the holding of all three hypotheses. All hypotheses were translated into statistical models, and their relative and absolute fit were assessed. Results provided strong evidence for hypothesis three: both the moderating role of decision accuracy on the relationship between rank-order distance and experienced complexity, and the relationship between experience and experienced complexity, were confirmed.